The Management of Head and Neck Sarcoma. Issue 2 (March 2020) - Han, Shengwei; Yin, Xiteng; Xu, Wenguang; Wang, Yufeng; Han, Wei
Abstract : Objective: To describe the incidence, types, features, treatment and outcomes of head and neck sarcoma managed at a treatment center in eastern China. Methods: Cases of head and neck soft tissue sarcoma and osteogenic sarcoma treated at the Stomatology Hospital of Nanjing University between 2008 and 2018 were retrospectively analyzed. Patient characteristics, site of lesion, main presenting symptoms, treatment, histology, local recurrence, development of metastatic disease, duration of follow-up and survival rates are described and compared. Results: Sixty-three patients were diagnosed with head or neck sarcoma of which 42.9% had soft tissue sarcoma and 57.1% had osteogenic sarcoma. Of soft tissue sarcoma patients, the most frequently observed histologies were fibrosarcoma and malignant fibrous histiocytoma. Of 36 cases of osteogenic sarcoma, osteosarcoma, and fibrosarcoma of bone were most frequent. Mean latency period between initial symptoms and clinical presentation was 4.5 months. Radical resection was performed on 56 patients. For 33 patients, resection and radiotherapy were used and 10 patients received a triple combination of resection, chemotherapy and radiotherapy. Within the observation period, 17 patients died. Conclusions: Head and neck sarcomas, although rare, can represent a variety of pathological diagnoses. Surgery remains the main intervention although the data suggest chemotherapy, radical resection and irradiation as treatment. Outcomes are poor with high rates of local recurrence. Positive prognostic factors were tumor-free resection margins and choice of therapy. Due to the rarity of head and neck sarcoma, information remains limited and choice of treatment should be within the focus of clinical multi-center studies. Abstract : Supplemental Digital Content is available in the text